Relapse of Pneumocystis carinii pneumonia in the upper lobes during aerosol pentamidine prophylaxis. - Bradburne, R M (1989)
Pneumocystis carinii pneumonia was diagnosed by bronchoalveolar lavage of the upper lobes in a patient with the acquired immunodeficiency syndrome (AIDS) receiving aerosol pentamidine prophylaxis. Serendipitous availability of a normal premorbid lung gallium scan indicated that pneumocystosis had developed during aerosol pentamidine prophylaxis; at the time of presentation a repeat gallium scan indicated disease limited to the upper lobes. The relation of this unusual form of isolated upper lobe Pneumocystis carinii pneumonia to aerosol pentamidine prophylaxis warrants further investigation.